2008
DOI: 10.1007/s10803-008-0647-6
|View full text |Cite
|
Sign up to set email alerts
|

Change Detection in Naturalistic Pictures Among Children with Autism

Abstract: Persons with autism often show strong reactions to changes in the environment, suggesting that they may detect changes more efficiently than typically developing (TD) persons. However, Fletcher-Watson et al. (Br J Psychol 97:537-554, 2006) reported no differences between adults with autism and TD adults with a change-detection task. In this study, we also found no initial differences in change-detection between children with autism and NVMA-matched TD children, although differences emerged when detection failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 45 publications
(63 reference statements)
5
24
0
Order By: Relevance
“…In the results presented here, no evidence was found of any difference between the capacity of individuals with ASD and IQmatched controls. This is similar to the findings of Fletcher-Watson et al (2006) who demonstrated that the ability to detect changes was equivalent in both ASD and control groups, and may also be consistent with Burack's work (Burack et al, 2009a) that suggests differences will only be seen when developmental level is taken into account. The absence of any increased level of visual short-term memory capacity would suggest that the increased distraction at high perceptual load seen in ASD in experiments one and two is not due to increased capacity.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the results presented here, no evidence was found of any difference between the capacity of individuals with ASD and IQmatched controls. This is similar to the findings of Fletcher-Watson et al (2006) who demonstrated that the ability to detect changes was equivalent in both ASD and control groups, and may also be consistent with Burack's work (Burack et al, 2009a) that suggests differences will only be seen when developmental level is taken into account. The absence of any increased level of visual short-term memory capacity would suggest that the increased distraction at high perceptual load seen in ASD in experiments one and two is not due to increased capacity.…”
Section: Discussionsupporting
confidence: 89%
“…A study by Fletcher-Watson et al (Fletcher-Watson et al, 2006), however, failed to show a difference between the ability of control individuals and individuals with ASD to detect changes in visual scenes. Likewise, Burack et al (2009a) also reported no difference in performance on a change detection task. However, when task performance was related to the developmental level of the participants a group difference emerged.…”
Section: Predictionsmentioning
confidence: 96%
See 2 more Smart Citations
“…Change within a particular face (such as in its expression or direction of gaze) rather than change from one face to another is arguably a more social and natural type of change and would be an important follow-up experiment to confirm the idea that children with autism lack an attentional bias for faces embedded in naturalistic scenes. Burack et al (2009) studied change detection of objects in children and found no difference in change detection ability in children with and without autism, but claimed a developmental trend toward improved performance in typical persons, but not in persons with autism (the authors did not statistically compare the error rate vs. mental age slopes of the two groups, however). It is important to investigate if a similar discrepancy in task performance between persons with and without autism spectrum disorders as a function of developmental level is found for detecting change over a wide range of social and non-social contexts.…”
Section: Introductionmentioning
confidence: 99%